Expanding Paramedic Scope of Practice in the Community: A Systematic Review of the Literature. (1st July 2013) - Bigham, Blair L.; Kennedy, Sioban M.; Drennan, Ian; Morrison, Laurie J.
Abstract Background. Paramedics are an important health human resource and are uniquely mobile in most communities across Canada. In the last dozen years, challenges in the delivery of health care have prompted governments from around the globe to consider expanding the role paramedics play in health systems. Utilizing paramedics for the management of urgent, low-acuity illnesses and injuries has been coined "community paramedicine, " but the role, safety, and effectiveness of this concept are poorly understood. Objective. We undertook a systematic review of the international literature to describe existing community paramedic programs. Method. We used the Cochrane methodology for systematic reviews. An international group of experts developed a search strategy and a health information specialist executed this search in Medline, Embase, and CINAHL starting January 1, 2000. We included all research articles in the English language that reported a research methodology. We excluded commentaries and letters to the editor. Two investigators independently screened citations in a hierarchical manner and abstracted data. Results. Of 3, 089 titles, 10 articles were included in the systematic review and one additional paper was author-nominated. The nature of the 11 articles was heterogeneous, and only one randomized controlled trial (RCT) was found. This trial showed community paramedicine to be beneficial to patients and health systems. The other articles drew conclusions favoring community paramedicine. Conclusion. Community paramedicine research to date is lacking, but programs in the United Kingdom, Australia, and Canada are perceived to be promising, and one RCT shows that paramedics can safely practice with an expanded scope and improve system performance and patient outcomes. Further research is required to fully understand how expanding paramedic roles affect patients, communities, and health systems. Key words: emergency medical services; prehospital; community paramedic; extended scope; paramedic practitioner